(untitled) (The International Conference on Sustainable Economics Management and Accounting Proceeding, 2026)
This study examines the effects of regional government expenditure on education, health, social protection, economic functions, and the Village Fund on the Human Development Index (HDI) and poverty, including indirect mechanisms through HDI. Using panel data from 29 regencies in Central Java during 2020–2024 analyzed via Structural Equation Modeling (SEM) in AMOS 23, the results show that education, health, social protection, and economic expenditures have no significant direct effects on the poverty rate, while the Village Fund has a positive and significant effect on poverty. Regarding HDI, health and economic expenditures have positive and significant effects, whereas education and social protection expenditures are insignificant, and the Village Fund has a negative and significant effect. Furthermore, HDI has a strong negative and significant effect on poverty, indicating that improvements in human development contribute substantially to poverty reduction. The mediation analysis shows that health and economic expenditures significantly reduce poverty indirectly through HDI, while education and social protection expenditures do not have significant indirect effects. In contrast, the Village Fund has a significant positive indirect effect on poverty through HDI, consistent with its positive direct effect and suggesting potential reverse causality and suboptimal allocation. These findings highlight the importance of strengthening health and economic spending to improve human capital and reduce poverty, while the effectiveness and targeting of education, social protection, and Village Fund allocations require further evaluation.